The Effect of Visitor Satisfaction Level on Willingness to Pay at Plengkung, in Alas Purwo National Park - Mona Annisa Matondang; Bahruni .; Rachmad Hermawan (Media Konservasi, 2017)
One of ecotourism destinations in Indonesia is located in the Plengkung Beach at Alas Purwo National Park, Banyuwangi, East Java. Plengkung is one of the world's best locations for surfing activities which can be equated with Hawaii, Australia and South Africa. It was attract tourists to visit Plengkung. Each investor should pay attention to visitor satisfaction in order to maintain and increase the number of visitors. However, visitor satisfaction could be reflected through the improvement of service quality. The purpose of this study was to measure the level of visitor satisfaction based on service quality at PT Plengkung Indah Wisata and PT Wanasari Pramudita Ananta in Plengkung, to measure the value of ecotourism satisfaction using the willingness to pay (WTP) approach and to know the effect of visitor satisfaction level on WTP after doing ecotourism activities. The research was conducted in June-October 2016 with data collection method using quesionnaires, interviews and literature studies. The effect of visitor satisfaction level on WTP of ecotourism activities in Plengkung was analyzed using bivariate correlation analysis (parson correlation coefficient) with p-value <0,05. The results showed that PT WPA had better service quality, hence it got higher satisfaction score which is 4,8. The WTP in PT WPA was greater than PT PIW, that is Rp 15.452.370 since PT WPA had a higher level of visitor satisfaction than PT PIW. The correlation test results proved that the level of visitor satisfaction significantly affect the WTP with a value of 0,031.Keyword: ecotourism, visitor satisfaction level, WTP.